Protein kinase A signaling regulates immune evasion by shaving and concealing fungal β-1,3-glucan - Arnab Pradhan; Olga A. Nev; Ian Leaves; Oleg A. Nev; Qinxi Ma; Gillian Milne; Grace Patterson; Mihai G. Netea; Lars P. Erwig; Rhys A. Farrer; Gordon D. Brown; Hugo A. van den Berg; et al. (Proceedings of the National Academy of Sciences, 2025)
Fungal pathogens infect billions and kill millions of people each year. Many of these pathogens have evolved strategies to evade our antifungal immune defenses. Candida albicans, for example, masks the proinflammatory pathogen-associated molecular pattern (PAMP) β-1,3-glucan, in response to specific host signals such as lactate. In C. albicans , most β-1,3-glucan lies in the inner cell wall shielded, by the outer mannan layer, from recognition by certain immune cells such as macrophages. β-1,3-glucan that becomes exposed at the cell surface can be shaved off by secreted enzymes. By integrating mathematical modeling with experimentation, we show that the dynamics of this shaving, together with the dynamics of β-1,3-glucan exposure during growth, can account for a range of β-1,3-glucan masking phenotypes. The mathematical model accurately simulates the dynamics of β-1,3-glucan exposure during growth and predicts levels of β-1,3-glucan shaving under a variety of conditions, revealing how subtle differences in growth contribute to observed variabilities in lactate-induced β-1,3-glucan masking. For example, clinical isolates previously thought to display minimal lactate-induced masking are shown to mask robustly. Using a range of C. albicans mutants, we confirm the importance of Gpr1/Gpa2-protein kinase A signaling for lactate-induced β-1,3-glucan shaving and define the contributions of the Xog1 and Eng1 glucanases to this shaving. Furthermore, examination of a shielding-defective C. albicans mnn2 x6 mutant confirms that both β-1,3-glucan shaving and shielding contribute to the dynamism of β-1,3-glucan masking at the fungal cell surface. Dynamism in PAMP masking is likely to be relevant to other fungal pathogens of humans.